2019
DOI: 10.3390/app9183935
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Based Classification of Mosquito Species: Comparison of Conventional and Deep Learning Methods

Abstract: This study aims to propose a vision-based method to classify mosquito species. To investigate the efficiency of the method, we compared two different classification methods: The handcraft feature-based conventional method and the convolutional neural network-based deep learning method. For the conventional method, 12 types of features were adopted for handcraft feature extraction, while a support vector machine method was adopted for classification. For the deep learning method, three types of architectures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Deep convolutional neural networks (DCNNs) of deep learning (DL) are state-of-the-art methods for object recognition and classification, including for agricultural pests and mosquito larva 8 , 9 . With feature extraction in the neural network layers, DL has a high potential to make the development of a model easier and more accurate 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep convolutional neural networks (DCNNs) of deep learning (DL) are state-of-the-art methods for object recognition and classification, including for agricultural pests and mosquito larva 8 , 9 . With feature extraction in the neural network layers, DL has a high potential to make the development of a model easier and more accurate 10 .…”
Section: Introductionmentioning
confidence: 99%
“…albopictus, that share significant morphological similarities. The issue was not focused on by the previous studies that came from the perspective of computer science, in which a dataset was mostly constructed by taking data from the internet (via data mining) 6 , 12 or images of the mosquito species that were in good condition 10 , 13 , 14 , which may make the model impractical when deployed on actual samples. Motta et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although the human classification accuracy measured in this study had low accuracy, some groups have shown the promise of recent advances in computer vision to provide a solution to the difficult problem of mosquito species identification [21,22]. These studies were limited to a small species set, which is not representative of the classification task in operational surveillance; however, these results warrant further evaluation of such computer vision methods on a larger, more representative species set.…”
Section: Discussionmentioning
confidence: 80%
“…Convolutional neural networks were used to classify mosquito species by images in the literature. While these research reports exceptionally high accuracy 38 41 , their method is usually based on consistently high-quality images, which are relatively rare in systems where images are taken by non-experts randomly selected. Others have created an automated way of taking photos of live mosquitoes and trained CNNs on the collected data 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%